Ectodysplasin A1 Deficiency Leads to Osteopetrosis-like Changes in Bones of the Skull Associated with Diminished Osteoclastic Activity - Schweikl, Christine; Maier-Wohlfart, Sigrun; Schneider, Holm; Park, Jung (International Journal of Molecular Sciences, 2022)
Pathogenic variants of the gene Eda cause X-linked hypohidrotic ectodermal dysplasia (XLHED), which is characterized by structural abnormalities or lack of ectodermal appendages. Signs of dysplasia are not restricted to derivatives of the ectodermal layer, but mesodermal abnormalities, such as craniofacial dysmorphism, are also frequently observed, suggesting close reciprocal interactions between the ectoderm and mesoderm; however, a causal link has remained unsubstantiated. We investigated the functional impact of defective ectodysplasin A1 (Eda1) signaling on postnatal bone homeostasis in Eda1-deficient Tabby mice. Interestingly, Eda1 was detected in wild-type mouse calvariae throughout postnatal lifetime. In calvariae, bone-lining Osterix (Osx)+ osteoblasts stained positive for Eda1, and osteoclasts were revealed as Eda receptor (Edar)-positive. Moreover, adult Eda1-deficient calvarial bone showed osteopetrosis-like changes with significantly diminished marrow space, which was maintained during adulthood. Concomitantly with osteopetrosis-like changes, Tabby calvarial bone and Tabby bone marrow-derived osteoclasts had far less osteoclastic activity-associated co-enzymes including cathepsin K, Mmp9, Trap, and Tcirg1 (V-type proton ATPase a3 subunit) compared with wild-type calvariae in vivo or osteoclasts in vitro, indicating that Eda1 deficiency may affect the activity of osteoclasts. Finally, we confirmed that nuclear Nfatc1-positive osteoclasts were strongly diminished during mature osteoclastic differentiation under M-CSF and RANKL in the Tabby model, while Fc-EDA treatment of Tabby-derived osteoclasts significantly increased nuclear translocation of Nfatc1. Furthermore, we identified enhanced Nfatc1 and NF-κB transcriptional activity following Fc-EDA treatment in vitro using luciferase assays. Overall, the results indicate that diminished expressions of osteoclastic activity-associated co-enzymes may lead to disturbed bone homeostasis in Tabby calvariae postnatally.
CRIS-Team Scopus Importer:2022-11-04
Keywords: bone; ectodermal dysplasia; ectodysplasin A1; NF-κB; NFAT; osteoclast differentiation; osteopetrosis